Response to Hans Thulesius and Vivian B. Martin on Ekins (2011) - Richard Ekins (Grounded Theory Review: An International Journal, 2011)
I appreciate the valuable comments from Hans Thulesius and Vivian Martin. Both reviewers usefully and most helpfully pinpoint salient issues to be considered in forging future routes for my ongoing research in jazz historiography.